2007
DOI: 10.1177/014860710703100126
|View full text |Cite
|
Sign up to set email alerts
|

Does Glutamine Supplementation Decrease the Response of Muscle Glutamine Synthesis to Fasting in Muscle in Adult and Very Old Rats?

Abstract: These results confirm that glutamine has a specific role in very old rats. The up-regulated GS activity was decreased by an exogenous supply of glutamine only if intramuscular glutamine was depleted; this was confirmed by studies in the fed state. The up-regulated GS activity in both fed and fasted rats may be associated with increased glutamine requirements in the whole body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…However, in the very old rats, decreased GS activity was only seen with Gln supplementation, with no effect of Gln supplementation observed in the fed state. In the very old rats, intramuscular Gln was depleted, resulting in the observed decrease in GS activity, in agreement with previous evidence indicating that sarcopenia is often associated with malnourishment [56].…”
Section: Supplementation With Glnsupporting
confidence: 92%
“…However, in the very old rats, decreased GS activity was only seen with Gln supplementation, with no effect of Gln supplementation observed in the fed state. In the very old rats, intramuscular Gln was depleted, resulting in the observed decrease in GS activity, in agreement with previous evidence indicating that sarcopenia is often associated with malnourishment [56].…”
Section: Supplementation With Glnsupporting
confidence: 92%
“…Only glutamine supplementation was able to significantly decrease glutamine synthetase activity in the skeletal muscle of very old rats (27 months), whereas supplementation with other amino acids decreased upregulated glutamine synthetase activity in adult rats. 143 Five-month supplementation in rats. Supplementation with glutamine was the same as that given previously but was an intermittent oral supplementation given during the last 5 months of life (7 consecutive days each month).…”
Section: Effect Of Glutamine Supplementation On Agingmentioning
confidence: 99%
“…Prolonged and strenuous exercise reduced circulating glutamine levels, possibly attributed to the enhanced uptake by the liver and other tissues and the reduced glutamine synthesis in the muscle [ 55 ]. A low level of circulating glutamine may reflect muscle loss, but glutamine supplementation does not seem to prevent sarcopenia [ 56 ]. Our data showed that glutamine level was positively associated with age.…”
Section: Discussionmentioning
confidence: 99%